Association between sports expertise and visual attention in male and female soccer players - Jin, Peng; Ji, Zheqi; Wang, Tianyi; Zhu, Xiaomin (PeerJ, 2023)
Background Visual attention plays a crucial role in daily living and in sports, affecting an athlete’s performance and thus, potentially, the outcome of a match. However, studies assessing the association between the level of sports expertise and visual attention have yielded mixed results. This study was conducted to examine whether visual attention could be developed with increased sports expertise, and whether visual attention differed between male athletes and female athletes. Methods A total of 128 participants were included in this study: 64 first-level national soccer athletes recruited from college soccer teams (considered elite athletes; 32 men and 32 women with similar soccer performance requirements and training experience), and 64 physical education college students with limited soccer experience (considered novice athletes; 32 men and 32 women with matched soccer experience). To assess visual attention, we used a multiple object tracking (MOT) task with four targets among a total of 10 objects moving at a fixed speed of 10°/s in random directions across a computer monitor screen. Tracking accuracy on the MOT task was calculated for each participant as the proportion of correctly selected targets. A univariate analysis of variance was performed, with group (expert, novice) and sex (male, female) as independent variables, and tracking accuracy on the MOT task as the dependent variable to assess whether sports expertise or sex influenced visual attention. Simple effects tests followed by comparisons with Bonferroni corrections were used, and effect size calculations were performed using Cohen’s f statistic. Results Tracking accuracy on the MOT task was significantly affected by sports expertise (F(1,124) = 91.732, p < 0.001, ηP2 = 0.425), with accuracy among expert soccer athletes superior to that among novice soccer athletes. Moreover, a statistically significant interaction between sports expertise and sex was detected (F(1,124) = 7.046, p = 0.009, η P2= 0.054). Better tracking performance was observed for male soccer players (mean [SD], 0.39 [0.12]) than for female soccer players (mean [SD], 0.27 [0.08]); p < 0.01; d=1.17; r = 0.51) but only in the novice group. No significant sex difference was detected in tracking performance between elite male soccer athletes (mean [SD], 0.51 [0.09]) and elite female soccer athletes (mean [SD], 0.49 [0.11]). Conclusion These findings confirm previous results indicating that long-term extensive sports training develops visual attention as assessed by MOT performance and extend previous findings to include soccer athletes. The findings of a sex difference in visual attention among novice soccer players but not among elite soccer athletes who had similar performance requirements and training experience suggest that long-term extensive training may minimize the sex difference in visual attention.
Keywords: Soccer player; Visual attention; Expertise; Sex difference; Multiple object tracking